Understanding the Limiting Factors of Solvent‐Annealed Small‐Molecule Bulk‐Heterojunction Organic Solar Cells from a Chemical Perspective. Issue 15 (21st July 2017) - Fernandez, Daniel; Viterisi, Aurelien; Challuri, Vijay; Ryan, James W.; Martinez‐Ferrero, Eugenia; Gispert‐Guirado, Francesc; Martinez, Marta; Escudero, Eduardo; Stenta, Caterina; Marsal, Lluis F.; Palomares, Emilio
Abstract: A detailed account of the limiting factors of solvent‐annealed bulk‐heterojunction small‐molecule organic solar cells is given. This account is based on the extensive characterisation of solar cell devices made from a library of five diketopyrolopyrole (DPP) donor dyes. Their chemical structure is designed in such a way as to provide insights into the energetics of solar cell active layer micro‐structure formation. Numerous chemical and physical properties of the active layers are assessed and inter‐related such as light absorption, molecular packing in the solid state, crystal‐forming properties in thin films, charge carrier mobility and charge carrier recombination kinetics. A myriad of characterisation techniques are used such as UV/Vis absorption spectroscopy, photoluminescence spectroscopy, XRD, AFM and photo‐induced transient measurements, which provide information on the optical properties of the active layers, morphology and recombination kinetics. Consequently, a mechanism for the solvent‐vapour‐annealing‐assisted formation of crystalline domains of donor molecules in the active layer is proposed, and the micro‐structural features are related to the J – V characteristics of the devices. According to this model, the crystalline phase in which the donor crystallise in the active layer is the key determinant to direct the formation of the micro‐structure. Abstract : Crystallite growth energetics : We give a detailed account of the limiting factors of a solvent‐annealed bulk‐heterojunction small‐molecule organic solar cell. A mechanism for the formation of crystalline domains of donor molecules in the active layer is proposed, and microstructure features are related to the J – V characteristics of the devices. The energetics of crystallite growth determine the establishment of a J – V characteristics–structure relationship.